Cation-Chloride Cotransporters, Na/K Pump, and Channels in Cell Water and Ion Regulation: In silico and Experimental Studies of the U937 Cells Under Stopping the Pump and During Regulatory Volume Decrease - Yurinskaya, Valentina E.; Vereninov, Alexey A. (Frontiers in Cell and Developmental Biology, 2021)
Cation-coupled chloride cotransporters play a key role in generating the Cl– electrochemical gradient on the cell membrane, which is important for regulation of many cellular processes. However, a quantitative analysis of the interplay between numerous membrane transporters and channels in maintaining cell ionic homeostasis is still undeveloped. Here, we demonstrate a recently developed approach on how to predict cell ionic homeostasis dynamics when stopping the sodium pump in human lymphoid cells U937. The results demonstrate the reliability of the approach and provide the first quantitative description of unidirectional monovalent ion fluxes through the plasma membrane of an animal cell, considering all the main types of cation-coupled chloride cotransporters operating in a system with the sodium pump and electroconductive K+, Na+, and Cl– channels. The same approach was used to study ionic and water balance changes associated with regulatory volume decrease (RVD), a well-known cellular response underlying the adaptation of animal cells to a hypoosmolar environment. A computational analysis of cell as an electrochemical system demonstrates that RVD may happen without any changes in the properties of membrane transporters and channels due to time-dependent changes in electrochemical ion gradients. The proposed approach is applicable when studying truly active regulatory processes mediated by the intracellular signaling network. The developed software can be useful for calculation of the balance of the unidirectional fluxes of monovalent ions across the cell membrane of various cells under various conditions.